Analysis and interpretation of mixture DNA using AS-PCR of mtDNA. Issue 1 (December 2019) - Wang, Bao-jie; Xu, Feng-ling; Ding, Mei; Yao, Jun; Wu, Xue; Xing, Jia-xin; Xuan, Jin-feng; Xia, Xi
Abstract: In forensic medicine, mixed stains usually include body fluids, secretions of two or more individuals. The application of STR profiling of single cell capture or mixed samples requires that the existence of intact nucleated cells or the appropriate proportion of different components in the sample, respectively. Trace components cannot be genotyped, and the analysis of mixture from more than two individuals is even more difficult. There are SNPs located in the mtDNA hypervariable region and its flanking sequences. According to the differences of SNPs between individuals, allele-specific PCR (AS-PCR) may be used to obtain the individual DNA fragments containing mtDNA hypervariable regions in mixed stains. There are two assumptions in the application of our method. One assumption is that when the suspect is known, the AS-PCR can be designed according to the SNPs in the mtDNA hypervariable and flanking regions. The suspect cannot be excluded if the amplified sequence is consistent with the suspect's. Otherwise, the suspect can be excluded. The other assumption is without the suspect. We can obtain the individual's sequence of the high component and then perform the multiple AS-PCR according to specific SNP. If the low component's fragment can be amplified, it is possible from the potential suspect. Our method is easy to conduct and can exclude the unrelated individuals or provide the suspect's information, especially for the individual with the low component. To some degree, it can solve the analysis of the mixture of multiple individuals. However, it is invalid for the samples of the same maternal line and the personal identification cannot be achieved. Our study is supported by National Natural Science foundation of China (NO.81671872).